HIV–1–specific fc–gamma–receptor– mediated effector functions: the role of host factors - Phaahla, Ntando Ghwenneth (My University, 2020)
Antibodies recruit potent innate immune effector functions through engagement of their Fc portion with Fc-gamma-receptors (FcγRs) expressed on the surface of effector cells. FcγR mediated effector functions such as the antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP) are mediated by binding antibodies, with immunoglobulin G (IgG) as the most predominant isotype. IgG occurs as four subclasses (IgG1-IgG4) that have distinct affinities for FcγRs and differentially regulate HIV-1-specific FγR-mediated effector functions. Effector cells further modulate FcγR-mediated effector functions through varied cellular distribution and expression of FcγRs. Although there is a consensus on the importance of Fc-mediated antibody function in protective immunity to HIV-1, less is known about the exact underlying mechanisms of HIV-1 prevention or replication control. This is due to the complex interaction of various host factors and the impact of chronic HIV-1 infection on these mechanisms. Therefore, we sought to characterize FcγR-mediated effector functions in HIV-1 infected Black South Africans (located in the region that is hardest hit by the AIDS epidemic), by assessing the modulatory effects of some host factors on these effector functions in the context of chronic HIV-1 infection and HIV-1 control. We investigated the cellular distribution of FcγRIIIa on cytotoxic lymphocytes – natural killer cells and CD8+ T cells – and the effect of the FcγRIIIa-F158V variant on ADCC capacity in HIV-1-infected individuals (n = 23) and healthy controls (n = 23) using the GranToxiLux ADCC assay (Chapter 2). Study participants were matched for F158V genotypes, carried two copies of the FCGR3A gene and were negative for expression of the inhibitory FcγRIIb on NK cells. We found that the distribution of CD56dimFcγRIIIabright and CD56negFcγRIIIabright NK cell subsets, but not FcγRIIIa surface expression, differed significantly between HIV-1 negative and HIV-1 positive donors. Intriguingly, healthy donors bearing at least one 158V allele had higher ADCC responses compared to those homozygous for the 158F allele, whereas the opposite was observed for the HIV-1-infected group, although the difference was not statistically significant. Furthermore, FcγRIIIa+CD8bright and FcγRIIIa+CD8dim T cell subsets were observed in both HIV-1 negative and HIV-1 positive donors, with median proportions that were significantly higher in HIV-1 positive donors compared to healthy controls. We demonstrate that CD8+ T cells acquire innate functions and can mediate HIV-1- specific ADCC through the delivery of granzyme B, which was overall lower compared to that of autologous NK cells. iv We next sought to investigate whether hypergammaglobulinaemia affects HIV-1-specific ADCC responses in individuals with different HIV-1 disease progression phenotypes (Chapter 3). Here, HIV-1 gp120-specific ADCC responses were compared and correlated with levels of total IgG and gp120-specific antibody isotypes and subclasses (IgM, IgA [IgA1-2] and IgG [IgG1-4]) in plasma obtained from 22 elite controllers, 35 viraemic controllers and 73 progressors. HIV-1-specific ADCC responses at low plasma dilutions, high concentrations of purified total IgG and high HIV-1-specific IgG were significantly reduced compared to higher dilutions of these antibody sources, thus exhibiting a prozone effect in the presence and in the absence of plasma constituents. Within this prozone window, ADCC responses were significantly higher in elite controllers compared to viraemic controllers and progressors. This is not attributable to higher HIV-1-specific IgG levels in elite controllers, since this group had significantly reduced total plasma IgG levels and gp120-specific IgG, IgG1, IgG2, IgG4, IgA1 and IgA2 compared to viraemic controllers and progressors. Conversely, elite controller ADCC responses at low plasma dilutions were inversely correlated with total plasma IgG levels, which suggests a regulatory effect of hypergammaglobulinaemia on this Fc effector function. In addition, CD4/CD8 ratios were directly correlated to ADCC responses in a subset of 20 controllers, with higher range CD4/CD8 ratio (>1) controllers mediating enhanced ADCC responses compared to those with lower range CD4/CD8 ratios (<1). The capacity of IgG to mediate HIV-1-specific phagocytosis and the role of antibody levels were subsequently determined for the same controller and progressor cohort (Chapter 4). Using the THP-1 phagocytic gp120-coated bead-uptake method in the presence of low (1 µg/ml) and high (50 µg/ml) concentrations of purified IgG, we observed that the median ADCP activity in elite controllers was significantly reduced compared to progressors at 1 µg/ml IgG, while there was no significant difference at 50 µg/ml IgG. ADCP responses at 1 µg/ml IgG, but not 50 µg/ml IgG, positively correlated with total plasma IgG levels. A modulatory effect of hypergammaglobulinemia may, thus, partly explain the ADCP differences observed between elite controllers and progressors at 1 µg/ml IgG, which is confounded by higher IgG concentrations in the assay used. Envelope gp120-specific IgG1 normalized for bulk plasma IgG was significantly elevated in elite controllers compared to progressors, while normalized gp120-specific IgG2 and IgG4 subclass levels were elevated in progressors compared to controllers. Furthermore, only the normalized gp120-specific IgG1 and IgG4 subclasses significantly positively associated with ADCP responses at 1 µg/ml and 50 µg/ml in the complete HIV-1 infected cohort. Although viral load and CD4+ T cell count v did not associate with ADCP responses, CD4/CD8 ratios were inversely correlated to ADCP responses at 1 µg/ml in a subset of 20 controllers, where those with <1 CD4/CD8 ratios mediating higher ADCP responses compared to controllers with >1 CD4/CD8 ratios. Therefore, Chapter 3 and 4 findings collectively suggest that immune hyper-activation that results in elevated antibody levels positively associates with ADCP responses as the disease progresses and yet the same phenomenon associates with a loss of ADCC activity in HIV-1 progressors. A comprehensive understanding of how these two possibly interdependent FcγR mediated effector functions are modulated during the course of an HIV-1 infection may contribute to the development of an effective HIV-1 vaccine or functional cure. Overall, this study underscores the need to characterize antibody levels and composition (Chapter 3 and 4), as well as FcγR expression, cellular distribution and functional consequences of FcγR genetic variants (Chapter 2) within a specific environment or disease state.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2020